A Preliminary Longitudinal Study on Infant-Directed Speech (IDS) Components in the First Year of Life - Flaviana Tenuta; Roberto Marcone; Elvira Graziano; Francesco Craig; Luciano Romito; Angela Costabile (MDPI AG, 2023)
Infant-directed speech (IDS) is an essential factor of mother-infant interaction and facilitates early language processing and word learning during dyadic interactions. This study aimed to longitudinally investigate emotional and prosodic components of IDS in the first year of life by analyzing children's responses to the different prosodic trends that mothers use during the observation of mother-child interactions. Seventeen mothers and infants were recruited for this study during their first hospitalization. The study involved observing communication changes in face-to-face interactions between the mother and child at three, six, and nine months after the child's birth. We analyzed the relationship between gaze direction, smiling, speech speed, and clarity. The results showed that the IDS differs in production when compared to the age of the child; at only nine months, there is high intensity. The same is evident from the results related to the elocution velocity. The verbal sensitivity of the mother and the ability to tune in to the affective states of the child, especially at nine months, can predict the child's understanding of future language.